(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Analyze a number of factors related to the knowledge of self-insulin injection of type 2 diabetes patients at Thanh Nhan hospital in 2024. Subjects and research methods: Cross-sectional description of over 150 patients aged 18 years and older diagnosed with type 2 diabetes according to the diagnostic criteria of ADA 2021, at the Department of Endocrinology and Metabolic Diseases, Thanh Nhan Hospital from April to August 2024 by ITQ (Injection Technique Questionnaire) was approved at the expert recommendation workshop (FITTER) and has been revised to suit the situation of Vietnam and in the opinion of experts. The toolkit is evaluated for reliability through Cronbach’s Alpha > 0.7. Results: The rate of insulin self-injection knowledge of patients has not reached 40%. This rate is higher in patients with education level ≤upper secondary school compared to >upper secondary school ( 64.8% compared to 36%); patients with complications compared to no complications (73% compared to 50.6%); patients with BMI ≥ 23 kg/m2 compared to < 23 kg/ m2 (70% compared to 48.7%); patients with disease detection time < 5 years compared to ≥5 years (87.5% compared to 56.7%). Conclusion: The patient’s knowledge of insulin injection is still high. Patients with lower-secondary school education, complications, BMI ≥ 23 kg/m2, disease detection time < 5 years have higher knowledge than patients with satisfactory knowledge.